A new species of Sicoderus Vanin from Bolivia (Coleoptera: Curculionidae: Curculioninae: Otidocephalini) - Vanin, Sergio A.; de Medeiros, Bruno A.s. (Zootaxa, 2013)
Sicoderus robini sp. nov. (type locality: Bolivia, Santa Cruz de la Sierra, Buena Vista, El Cairo) is described and illustrated. The new species is assigned to the Sicoderus appendiculatus species group, compared with similar species of the group and with the two other species of Sicoderus that occur in Bolivia. The previously published key for species identification of the S. appendiculatus group is updated to include the new species.